Guide to Culturally Responsive Teaching and Diverse Learners in the Daily Life of Schools - Paksuniemi, Merja; Körkkö, Minna; Keskitalo, Pigga; Norvapalo, Katja (Siirtolaisuusinstituutti, 2020)
The purpose of this booklet, Guide to culturally responsive teaching and diverse learners in the daily life of schools, is to increase research-based knowledge of culturally responsive teaching and offer practical examples that can be used in primary school teacher training and when tutoring and teaching learners with a diverse needs and minority or immigrant backgrounds. The name of this booklet derives from the idea, shared by the three projects, of applying culturally responsive teaching in the daily activities of teachers and schools. This guide is a response to the need to manage increasingly diverse teaching contexts. Teachers and primary school student teachers need information about the theory and practice of culturally responsive teaching in order to manage complex learning and teaching situations. The authors of this guide are experts from the three projects as well as invited writers. Authors and editors Preface I Culturally Responsive Teaching Culturally Responsive Teaching Strategies / Merja Paksuniemi Culturally Responsive Teaching in Sámi Education / Pigga Keskitalo The Contents and Methods of Inclusive Pedagogy / Suvi Lakkala II Culturally Responsive Teaching Practices Mentoring in School Transitions / Minna Körkkö Factors Afecting Young Immigrants’ Education Choices / Elli Heikkilä Young Immigrants’ Transition to Upper Secondary Education / Heidi Keskinen Teaching Thinking Skills in Basic Education / Outi Kyrö-Ämmälä & Katja Anttila Enhancing the Inclusion of Immigrant Pupils / Satu Taskinen.